An Automated BIM-Based System for Generating Shop Drawings and Material Takeoffs: A Case Study of Ceiling Work - Thearith, Sonya; Peansupap, Vachara; Tongthong, Tanit (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
During the construction phase, the detail shop drawing and material takeoff are required for supporting construction operations. These processes are labor intensive and take longer time. Recently, the implementation of Building Information Modeling (BIM) technology is an approach that can be used to assist in shop drawing and accurate material takeoff. However, the traditional method of using two-dimensional drawings is still extensively applied to various current practices, which is time-consuming and error prone. Furthermore, previous BIM technology was limited to performing material takeoff for building elements consisting of multiple material layers. This paper proposes a BIM-based automated system for generating detailed shop drawings and material quantities. This research focuses on developing systems for ceiling work. To develop the system, the design algorithm for the ceiling frame and fixed light system is formalized according to the provided construction layout plan. Then, the concept of BIM-based clash detection is applied to automatically detect the overlap between the fixed light system and ceiling frame. A prototype system is being developed in BIM technology that is integrated with Dynamo. An apartment room ceiling layout is utilized to determine the feasibility and effectiveness of the proposed system. The result indicates that the proposed system can automatically generate clear shop drawings in accordance with the designed standard, which provides more accurate material takeoff for C-line and gypsum board in the ceiling system. Moreover, the system will assist engineers in resolving purchase order conflicts during the construction stage as it can automatically generate the quantity of materials based on standard material product sizes.